Assessment and comparison of the housing needs and aspirations of urban and rural elderly in Malaysia / Nooraisyilah Murni - Nooraisyilah, Murni (2017)
The ageing phenomenon in Malaysia is inevitable due to the exponential increase in the elderly population. Additionally, Malaysia is also experiencing rapid urban population growth. Due to the rapid pace of urbanisation and its impact towards the population, it becomes increasingly necessary to look into the effects of urbanisation towards elderly and their housing aspect. A careful evaluation of the needs of elderly is required to best prepare countries for the challenges and opportunities that the elderly population would be facing. Understanding the key issues surrounding the needs of Malaysia elderly community is crucial for reforming the existing policy and related elderly service provision framework. Thus, this study aims to examine the key issue relating to elderly housing in Malaysia. Specifically, it seeks to identify differences between housing needs of elderly living in urban and rural areas in Malaysia. This study uses the questionnaire survey, as its main tool to gather data. Stratified sampling based on age and ethnicity was used to obtain the data. The selected urban area for this study is Kuala Lumpur Federal Territory whereas, Kelantan rural area is selected as the rural area for this study. The main academic benefit of this research is to add insight into a new area of housing research i.e elderly urban-rural housing needs. As for practical contribution, this study offers policymakers a chance to explore more into the housing needs of elderly with respect to their urban-rural aspects. Findings from this study suggest that both the urban and rural elderly in Malaysia still consider the ‘age-in-place’ as their main housing options. Older age group of elderly indicates that they are less concern to move, regardless of whether they are urban or rural elderly. Results indicate that in terms of housing, the urban elderly needs safer kitchen and bathroom area. On a similar point, rural elderly emphasise on their need for the safer bathroom area. Contrastingly, rural elderly seems to view that they need a safer staircase. Results also revealed that elderly living in the urban area need environments that are safer and are of better air quality. Whereas, elderly in the rural area indicates that they need cleaner environment. The finding suggests that adequate attention is given towards the safety of the urban elderly. With this finding, it is recommended that a policy is developed to promote ageing-inplace which considers attitudes, opinions and preferences of elderly in Malaysia.